Pedagogical Challenges of Transhumanism: Possible Threats in the Context of Digitalization - Vorontsova, Yulia; Gil Martínez, Maria Adelaida; Arakelyan, Artur; Yeremyan, Ara (Տիգրան Մեծ)
The article focuses on issues related to the pedagogical challenges of transhumanism. The authors consider possible ways to ensure that students will have a high level of economic literacy in combination with morality. This will allow students to develop an idea of ethical consequences which arise from man-agement decisions made in the context of digitalization. When teachingsubjects related to economic cycles,a lecturer faces various challenges formed by the modern transhumanist concept. One of the challenges is to work with the “digital generation” without its knowledge and orientation to moral and ethical principles, especially when students are from non-humanitarian universities. The ability to feel and be aware of fairness and to prefer justice to unjustness is a characteristic gifted to a human being to maintain his or her own internal interests. Transferring this attitude to the company will influence and form its ethical and moral principles in creating and promoting a product aimed at removing the obstacles associated with physical inability. Ethical postulates in teaching economic disciplines will ensure that students realize the concept of acceptable limits for generating income from technological innovations in various sectors of digital economics. In addition, the article presents the advantages and disadvantages of such concepts as variability and alternative education, its national character, continuous education, and intercultural communication.
Keywords: Philosophy of education